2023
DOI: 10.1007/s10151-023-02809-y
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of perianal fistula using an ovine forestomach matrix implant

Abstract: Purpose Invasive surgical management of cryptoglandular perianal fistulas (PF) is challenging because of high recurrence rates and the potential for injury to the sphincter complex. In the present technical note, we introduce a minimally invasive treatment for PF using a perianal fistula implant (PAFI) comprising ovine forestomach matrix (OFM). Methods This retrospective observational case series highlights 14 patients who had undergone a PAFI procedure at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
(18 reference statements)
0
0
0
Order By: Relevance
“…With no consensus on a standard surgical approach, traditional and biologic stula plugs, or implants, have been an increasingly common reported solution [9]. In this study, OFM was used as a PAFI due to its demonstrated ability to augment healthy soft tissue regeneration in chronic defects, its ease of use, low cost, and demonstrated previous e cacy as a PAFI [20]. In this retrospective case series of 25 patients, OFM was able to achieve healing and maintain closure in 76% (n = 19) of cases at 12-weeks with a median healing time of 4.5 weeks with a median single application (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With no consensus on a standard surgical approach, traditional and biologic stula plugs, or implants, have been an increasingly common reported solution [9]. In this study, OFM was used as a PAFI due to its demonstrated ability to augment healthy soft tissue regeneration in chronic defects, its ease of use, low cost, and demonstrated previous e cacy as a PAFI [20]. In this retrospective case series of 25 patients, OFM was able to achieve healing and maintain closure in 76% (n = 19) of cases at 12-weeks with a median healing time of 4.5 weeks with a median single application (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, biologic stula plugs have demonstrated success in limiting incontinence and surgical complications but exhibit varying degrees of clinical e cacy. More recently, a biologic implant derived from ovine forestomach matrix (OFM) has been studied as a novel alternative to the traditional plugs with promising early success [20]. OFM is a decellularized extracellular matrix (dECM) that preserves inherent tissue architecture and retains biomolecules crucial to the tissue regeneration process [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation